2016
DOI: 10.1002/glia.23041
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 drives microglia and macrophages toward a phenotype conducive for tissue repair and functional recovery after spinal cord injury

Abstract: "This is the peer reviewed version of the following article: Francos-Quijorna I, Amo-Aparicio J, Martinez-Muriana A, López-Vales R. IL-4 drives microglia and macrophages toward a phenotype conducive for tissue repair andfunctional recovery after spinal cord injury. Glia. 2016 Dec;64(12):2079-2092 ABSTRACTMacrophages and microglia play a key role in the maintenance of nervous system homeostasis.However, upon different challenges, they can adopt several phenotypes, which may lead to divergent effects on tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
135
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(145 citation statements)
references
References 39 publications
7
135
0
Order By: Relevance
“…Microglia, the resident macrophages of the central nervous system (CNS; Nakamichi et al, 2013; Ginhoux and Prinz, 2015), constitute 10%–15% of brain cells and play a critical role in CNS homeostasis (Solé-Domènech et al, 2016). Previous studies demonstrated that microglia polarizes into two states, M1 like phenotype and M2 like phenotypes (Francos-Quijorna et al, 2016; Lee et al, 2016). M1 like phenotype microglia is related with pro inflammatory response’s induction, whereas M2 like phenotype microglia is associated with neuroprotective roles (Eggen et al, 2013; Gertig and Hanisch, 2014; Natoli and Monticelli, 2014; Plastira et al, 2016; Xu et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Microglia, the resident macrophages of the central nervous system (CNS; Nakamichi et al, 2013; Ginhoux and Prinz, 2015), constitute 10%–15% of brain cells and play a critical role in CNS homeostasis (Solé-Domènech et al, 2016). Previous studies demonstrated that microglia polarizes into two states, M1 like phenotype and M2 like phenotypes (Francos-Quijorna et al, 2016; Lee et al, 2016). M1 like phenotype microglia is related with pro inflammatory response’s induction, whereas M2 like phenotype microglia is associated with neuroprotective roles (Eggen et al, 2013; Gertig and Hanisch, 2014; Natoli and Monticelli, 2014; Plastira et al, 2016; Xu et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…rM showed to increase M2 marker CD206 and anti-inflammatory molecules (IL-10 and PGD 2 ) expression, along with M1 markers including NOS-2, COX-2 (Bystrom et al 2008). Moreover, new evidence has emerge showing that after spinal cord injury, exogenous IL-4 treatment increase the population of M2 phenotype, but it also appeared another population of cells suggesting to be infiltrating macrophages with a mixed phenotype co-expressing M1 markers (NOS-2, COX-2, LOX, CD16/32) and M2 markers (Arg-1, CD206) as well as anti-inflammatory cytokines IL-10 and TGFβ1 and were associated with rM, known to be important in the resolving of inflammation (Francos-Quijorna et al 2016). Even though the phenotype markers and cytokines expressed after BAY41+Sil treatment in our cerebellar slices is very similar to those observed in the rM, our treatment in this model despite increasing Arg-1 failed in promoting CD206; moreover no expression of NOS-2 or any other proinflammatory molecule besides COX-2 was observed.…”
Section: Discussionmentioning
confidence: 89%
“…The therapeutic potential of exogenous IL4 has been well documented in several CNS pathology models including models for spinal cord injury (Lee et al, 2010; Francos-Quijorna et al, 2016), APP/PS1 transgenic mice (Kiyota et al, 2010), cerebral ischemia (Zhao et al, 2015; Liu et al, 2016) as well as multiple sclerosis (Butti et al, 2008). In these studies, IL4 was either injected or overexpressed in CNS tissues and promoted strong neuroprotective and anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…M2-like microglia activation is induced by the Th2 cytokines Interleukin 4 (IL4) and Interleukin 13 (IL13) and characterized by upregulation of alternative activation markers Arginase-1 (Arg1) and Chitinase 3 like 3 (Ym1) (Colton and Wilcock, 2010; Zhou et al, 2012). IL4-induced M2-like microglia/macrophage activation has been described to exert neuroprotective effects in mouse models for spinal cord injury (Francos-Quijorna et al, 2016), cerebral ischemia (Liu et al, 2016) and multiple sclerosis (Butti et al, 2008). Next to the abovementioned CNS pathologies, M2-like microglia activation has been further described in animal models of Parkinson’s disease (PD) and has been associated with reduced progression and disease severity (Moehle and West, 2015).…”
Section: Introductionmentioning
confidence: 99%